1997
DOI: 10.1021/js950346l
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Transdermal Penetration of a Series of Nonsteroidal Antiinflammatory Drugs

Abstract: The transdermal absorption of a series of nonsteroidal antiinflammatory drugs (NSAIDs): indomethacin, ketoprofen, diclofenac, piroxicam, tenoxicam, ketorolac, and aceclofenac) was studied in vitro with human skin. The purpose of the study was to determine the permeation parameters (permeability rate constant, Kp; lag time, TL, and flux, J) as measures of the intrinsic transdermal permeabilities of these drugs to predict their potential for formulation in a transdermal therapeutic system (TTS). A linear correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(94 citation statements)
references
References 21 publications
(15 reference statements)
5
81
0
5
Order By: Relevance
“…The solubility curves of PX (form I) in methanol and ethanol were determined, with values determined for the latter found to be consistent with previous literature reports of PX solubility 19,20 . The curves are similar in shape, with PX less soluble in ethanol throughout the temperature range ( Figure 12).…”
Section: Solubility Of Multi-component Molecular Crystals Of Pxsupporting
confidence: 86%
“…The solubility curves of PX (form I) in methanol and ethanol were determined, with values determined for the latter found to be consistent with previous literature reports of PX solubility 19,20 . The curves are similar in shape, with PX less soluble in ethanol throughout the temperature range ( Figure 12).…”
Section: Solubility Of Multi-component Molecular Crystals Of Pxsupporting
confidence: 86%
“…Six replicates were used for the concentrations of n-octanol-distilled water solutions for partition coefficient calculations. 20 The same experiment was repeated using soybean oil as an organic phase. 19 …”
Section: Determination Of Drug Solubilitymentioning
confidence: 99%
“…Idson (1975) demonstrated that the epidermic barrier was the limiting factor for the percutaneous absorption and that once the drug passed through the stratum corneum of the epidermis, its absorption was guaranteed. Currently, the study of percutaneous absorption has been a priority in the pharmaceutical research as it presentes an alternative route for drug administration, overcoming some of the disadvantages of oral administration, such as the hepatic first-pass effect, or other adverse effects (Cordeiro et al, 1997;Finnin and Morgan, 1999;Idson, 1975;Kitagawa et al, 1998).…”
Section: History and Prospectsmentioning
confidence: 99%